Formation and relaxation kinetics of starch–particle complexes. Issue 47 (17th November 2016) - Iselau, Frida; Phan Xuan, Tuan; Trefalt, Gregor; Matic, Aleksandar; Holmberg, Krister; Bordes, Romain
Abstract : The formation and relaxation kinetics of starch–particle complexes were investigated in this study. Abstract : The formation and relaxation kinetics of starch–particle complexes were investigated in this study. The combination of cationic nanoparticles in suspension and anionic starch in solution gave rise to aggregate formation which was studied by dynamic light scattering, revealing the initial adsorption of the starch molecules on the particle surface. By examining the stability ratio, W, it was found that even in the most destabilized state, i.e. at charge neutralization, the starch chains had induced steric stabilization to the system. At higher particle and starch concentrations relaxation of the aggregates could be seen, as monitored by a decrease in turbidity with time. This relaxation was evaluated by fitting the data to the Kohlrausch–Williams–Watts function. It was found that irrespective of the starch to particle charge ratio the relaxation time was similar. Moreover, a molecular weight dependence on the relaxation time was found, as well as a more pronounced initial aggregated state for the higher molecular weight starch. This initial aggregate state could be due to bridging flocculation. With time, as the starch chains have relaxed into a final conformation on the particle surface, bridging will be less important and is gradually replaced by patches that will cause patchwise flocculation. After an equilibration time no molecular weight dependence on aggregation could be seen, which confirms the patchwise flocculation mechanism.